Failure modes of spot welds in quasi – static tensile – shear loading of coated steel sheets. (2017) - Boriwal, L.; Sarviya, R.M.; Mahapatra, M.M.
Abstract: Failure modes of resistance spot welds of steel sheet largely depends upon the complex interplay between the weld geometry, fusion zone and heat affected zone. Steel sheet are potential material for automobile industry and aerospace. The present article investigates the mode of failure of resistance spot welded joints of 0.8 mm thickness sheet by tensile observed. There is critical fusion size to ensure nugget pullout failure mode in tensile- shear test. Scanning electron microscope (SEM) images shows that the failure mode are partially pullout and partially interfacial.